Data and Information Security in a Global Age - Yinka, Akintunde Michael (Mediterranean Journal of Social Sciences, 2011)
Having observed carefully the dynamics of e- activity and technology in business, finance and other realms of humanendeavour, the issue of data and information security with computer networks becomes more relevant in order to keep up withthe growing trend, hence the need to carefully address some important issues concerning data and information security.Information and data security, computer security are often incorrectly used interchangeably. These fields are interrelated oftenand share the common goals of protecting confidentiality, integrity and availability of information .Computer security can focus onensuring the availability and correct operation of a computer system without concern for the information stored or processed bythe computer. Governments and other realms of human endeavour amass a great deal of confidential information about theiremployees, customers, products, research and financial status. Most of this information is now collected, processed and storedon electronics computers and transmitted across networks to other computer. Protecting confidential information is a businessrequirement and in various cases also an ethical and legal requirement. This article presents a general overview of informationand data security and its core concepts in this era where e- activity and technology has been the prevailing trends in gettingthings done throughout the world.